2021
DOI: 10.1186/s12940-020-00687-7
|View full text |Cite
|
Sign up to set email alerts
|

Short-term exposure to air pollution and hospital admission for pneumonia: a systematic review and meta-analysis

Abstract: Background Air pollution is a major issue that poses a health threat worldwide. Although several studies investigated the adverse effects of air pollution on various diseases, few have directly demonstrated the effects on pneumonia. Therefore, we performed a systematic review and meta-analysis on the associations between short-term exposure of air pollutants and hospital admission or emergency room (ER) visit for pneumonia. Methods A literature sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 62 publications
2
20
1
Order By: Relevance
“…Dominici et al (2006) [13] report PM 2.5 -related RR for hospital admissions due to COPD at the level of 1.0091 (95% CI, from 1.0018 to 1.0164), while, in the review by DeVries et al (2016) [36], the RR of COPD hospitalization ranged from 1.014 to 1.025 per 10 µg/m 3 of PM 2.5 . The RR value obtained in a worldwide meta-analysis [34] for admissions due to pneumonia (all ages) equaled 1.010 (95% CI, from 1.005 to 1.015). In the study of Liu et al (2019) [15], RS mortality due to PM 2.5 exposure was associated with RR = 1.0074 (95% CI, from 1.0053 to 1.0095).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Dominici et al (2006) [13] report PM 2.5 -related RR for hospital admissions due to COPD at the level of 1.0091 (95% CI, from 1.0018 to 1.0164), while, in the review by DeVries et al (2016) [36], the RR of COPD hospitalization ranged from 1.014 to 1.025 per 10 µg/m 3 of PM 2.5 . The RR value obtained in a worldwide meta-analysis [34] for admissions due to pneumonia (all ages) equaled 1.010 (95% CI, from 1.005 to 1.015). In the study of Liu et al (2019) [15], RS mortality due to PM 2.5 exposure was associated with RR = 1.0074 (95% CI, from 1.0053 to 1.0095).…”
Section: Discussionmentioning
confidence: 92%
“…The WHO HRAPIE report [33] indicates PM 10 -related RR only for the incidence of asthma symptoms in asthmatic children aged 5-19 years, and this is 1.028 (95% CI, from 1.006 to 1.051). A recent meta-analysis by Yee et al (2021) [34] for hospitalization due to pneumonia reports RR at the level of 1.004 (95% CI, from 1.002 to 1.006) per 10 µg/m 3 of PM 10 . RS mortality due to PM 10 exposure was associated with RR = 1.0047 (95% CI, from 1.0035 to 1.0058) in the study of Liu et al (2019) [15].…”
Section: Relative Risk Of Cardiovascular and Respiratory Hospital Adm...mentioning
confidence: 99%
“…Chronic obstructive pulmonary disease (COPD) exacerbations were also related to poor air quality (Boehm et al 2021). A metaanalysis including 21 studies showed that with every 10 μg/ m 3 increment in PM 2.5 and PM 10 , the increase in ED admissions for pneumonia were 1.0% (95% CI 0.5-1.5) and 0.4% (95% CI 0.2-0.6), respectively (Yee et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The indicated risk, however, can be controlled through enhanced environmental cleaning and disinfection procedures [ 27 ]. Currently, hospital air quality is recognised as an important determinant in preventing airborne transmission of HCAIs [ 28 ] and ambient air pollution is a well-established risk factor of community-acquired pneumonia in both adults [ 29 , 30 ] and children [ 31 , 32 , 33 ]. The distributions and compositions of air streams as well as their microbial contamination are determined by the amount and velocity of natural ventilation [ 28 , 34 , 35 ]; implementation of sophisticated mechanical ventilation systems [ 28 , 35 ]; differential regulation of air pressure [ 35 ]; efficiency of air filtration [ 35 ]; indoor air temperature [ 35 ]; and relative humidity [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different-sized PM fractions have distinct penetration depths: Coarse PM (PM 10 or PM 2.5–10 having aerodynamic diameter between 2.5 and 10 µm) are retained in the upper airways, while fine PM (PM 2.5 or PM 0.1–2.5 having aerodynamic diameter between 0.1 and 2.5 µm) reaches the alveoli, and ultrafine PM (PM 0,1 having aerodynamic diameter ≤0.1 µm) might trespass the blood–air barrier and enter the circulation [ 42 ]. Accordingly, PM 0.1–2.5 is predominant in the lungs and is mainly responsible for pneumonia [ 29 , 30 ] and chronic obstructive pulmonary disease [ 43 , 44 , 45 ], while PM 2.5–10 is primarily associated with upper respiratory tract infections [ 46 , 47 ]. Despite the well-defined role of PM in respiratory diseases, the role of hospital PM as a vehicle for bacterial and viral agents causing HCAIs has been largely neglected to date, albeit the critical reviews suggested the potential importance of ventilation system contamination in the spread of HCAIs [ 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%